(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
In this article, the processes of training qualified personnel for the labor market by teaching foreign languages to young people are classified. At the same time, data on ensuring their employment by training them in professions that are in high demand in the domestic and foreign labor markets and teaching them foreign languages was analyzed. Proposals and recommendations have been developed to ensure employment of young people in the domestic and foreign labor market by teaching foreign languages and vocational training in educational institutions.